Effect of compaction on microbial activity and carbon and nitrogen transformations in two oxisols with different mineralogy - Sérgio Ricardo Silva; Ivo Ribeiro da Silva; Nairam Félix de Barros; Eduardo de Sá Mendonça (Revista Brasileira de Ciência do Solo, 2011)
The use of machinery in agricultural and forest management activities frequently increases soil compaction, resulting in greater soil density and microporosity, which in turn reduces hydraulic conductivity and O2 and CO2 diffusion rates, among other negative effects. Thus, soil compaction has the potential to affect soil microbial activity and the processes involved in organic matter decomposition and nutrient cycling. This study was carried out under controlled conditions to evaluate the effect of soil compaction on microbial activity and carbon (C) and nitrogen (N) mineralization. Two Oxisols with different mineralogy were utilized: a clayey oxidic-gibbsitic Typic Acrustox and a clayey kaolinitic Xantic Haplustox (Latossolo Vermelho-Amarelo ácrico - LVA, and Latossolo Amarelo distrófico - LA, respectively, in the Brazil Soil Classification System). Eight treatments (compaction levels) were assessed for each soil type in a complete block design, with six repetitions. The experimental unit consisted of PVC rings (height 6 cm, internal diameter 4.55 cm, volume 97.6 cm³). The PVC rings were filled with enough soil mass to reach a final density of 1.05 and 1.10 kg dm-3, respectively, in the LVA and LA. Then the soil samples were wetted (0.20 kg kg-1 = 80 % of field capacity) and compacted by a hydraulic press at pressures of 0, 60, 120, 240, 360, 540, 720 and 900 kPa. After soil compression the new bulk density was calculated according to the new volume occupied by the soil. Subsequently each PVC ring was placed within a 1 L plastic pot which was then tightly closed. The soils were incubated under aerobic conditions for 35 days and the basal respiration rate (CO2-C production) was estimated in the last two weeks. After the incubation period, the following soil chemical and microbiological properties were detremined: soil microbial biomass C (C MIC), total soil organic C (TOC), total N, and mineral N (NH4+-N and NO3--N). After that, mineral N, organic N and the rate of net N mineralization was calculated. Soil compaction increased NH4+-N and net N mineralization in both, LVA and LA, and NO3--N in the LVA; diminished the rate of TOC loss in both soils and the concentration of NO3--N in the LA and CO2-C in the LVA. It also decreased the C MIC at higher compaction levels in the LA. Thus, soil compaction decreases the TOC turnover probably due to increased physical protection of soil organic matter and lower aerobic microbial activity. Therefore, it is possible to conclude that under controlled conditions, the oxidic-gibbsitic Oxisol (LVA) was more susceptible to the effects of high compaction than the kaolinitic (LA) as far as organic matter cycling is concerned; and compaction pressures above 540 kPa reduced the total and organic nitrogen in the kaolinitic soil (LA), which was attributed to gaseous N losses.